Fatty acid composition, antioxidant, anti-inflammatory and antibacterial activities of seed oil from Crotalaria juncea Linn. - Chouhan H.S.; Sahu A.N.; Singh S.K. (My University, 2025)
Chemical characteristics, fatty acid composition, antioxidant, anti-inflammatory and antibacterial activities of Crotalaria juncea seed oil (CJSPE) were evaluated in this study. High amount of linoleic acid (62.36%) was found in CJSPE by the gas liquid chromatography (GLC) study. Antioxidant activity of CJSPE was evaluated by in vitro assay methods which revealed the 2,2-Diphenyl-1-picrylhydrazyl (DPPH), hydroxyl and superoxide radical scavenging activity of CJSPE; its antioxidant activity was found to be concentration dependent and IC50 values were 132.31, 286.409 and 31.254 g/ml respectively. Moreover, CJSPE has displayed dose dependant, significant inhibition of NO production in the isolated rat peritoneum macrophages; and significant anti-inflammatory activity in carragennaninduced paw edema (64.52 ± 0.053%, p < 0.001, at 6 h, 200 mg/kg oral dose) and cotton pellet-induced granuloma formation (48.55 ± 0.244%, p < 0.001, at 200 mg/kg oral dose) models of inflammation; and its anti-inflammatory effect was comparable to that of diclofenac sodium. However, moderate antibacterial activity of CJSPE was observed. In conclusion, the study demonstrated significant antioxidant and anti-inflammatory activities of CJSPE. ©2011 Academic Journals.